(untitled) (LACCEI, 2024)
This article presents the results of an exploratory study on the development of investigative skills in students of different cycles of the Industrial Engineering career. Various models of investigative competencies are presented, but the one by Veytia et al. (2019) for using competency indicators specifically with the use of technology, a factor that today cannot be ruled out. It is remarkable to identify the weaknesses that students present in the development of investigative skills. It is necessary to review and rethink the curricular proposal to ensure optimal development of these.